2022
DOI: 10.1021/acscatal.1c04854
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Support Interactions in Metal/Oxide Catalysts and Oxide–Metal Interactions in Oxide/Metal Inverse Catalysts

Abstract: Solid catalysts usually consist of multicomponents, within which interfacial interactions have been recognized as a key factor affecting structures and catalytic performance. Metal−support interactions (MSI) have been extensively studied in oxidesupported metal catalysts (metal/oxide catalysts), in which the important concepts of strong metal−support interactions (SMSI) and electronic metal−support interactions (EMSI) have been well established and their effects on the metal catalysis have been extensively dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(151 citation statements)
references
References 194 publications
(333 reference statements)
5
119
0
Order By: Relevance
“…However, the increase in the chemidissolution timescales on the UQG ITO led us to speculate that contact between the gold and the UQG ITO shifted the chemical potential of the metal, increasing the activation barrier for the chemidissolution process and slowing the associated kinetics. Similar substrate effects have been reported on other systems, [46,47] and we are currently working to understand this effect in more detail. This result once again highlights how electrochemical contact with a supporting substrate can impact the behavior of nanoparticles, even when monitoring solution‐phase redox reactions, highlighting the importance of comparing sample behavior across different substrates before drawing quantitative structure‐function conclusions.…”
Section: Resultssupporting
confidence: 77%
“…However, the increase in the chemidissolution timescales on the UQG ITO led us to speculate that contact between the gold and the UQG ITO shifted the chemical potential of the metal, increasing the activation barrier for the chemidissolution process and slowing the associated kinetics. Similar substrate effects have been reported on other systems, [46,47] and we are currently working to understand this effect in more detail. This result once again highlights how electrochemical contact with a supporting substrate can impact the behavior of nanoparticles, even when monitoring solution‐phase redox reactions, highlighting the importance of comparing sample behavior across different substrates before drawing quantitative structure‐function conclusions.…”
Section: Resultssupporting
confidence: 77%
“…Metal–support interfaces are particularly important in designing highly efficient FTS catalysts. ,, It is suggested that the metal–support interaction (MSI) would influence the dispersion, reduction, and activation behavior of the active metal phase. The role of MSI can be attributed to the electronic and geometric effect. , On one hand, the charge transfer between the support and metal would produce a strong ionic bond and simultaneously change the electronic density of the active metal. On the other hand, the metal surface coverage of a thin layer of reducible oxides or the formation of an inactive metal–support spine compound (i.e., CoAl and CoSi) would change the geometric structure of the active site.…”
Section: Traditional Fischer–tropsch Synthesismentioning
confidence: 99%
“…The shift of the N 1s peak to lower binding energy in BCET2 compared to the BT sample by 0.02 eV proves the engagement of BN nanosheets with Ce2O3 and TiO2 nanofibers [8]. According to the reported literatures [65], [66], [67], Ce2O3 will be stabilized through interaction by metal (Ag) and the charge transfer can stabilize Ce2O3. According to our results, there is charge transfer between Ce-Ti, and this interaction has stabilized Ce in +3 oxidation state.…”
Section: (1 H and I)mentioning
confidence: 68%